Self-Portrait. - Saar, Johannes; Institute for Contemporary Arts, Moscow (Tallinn : Estonian Artists Association, 1995)
Allik, Peeter ; Myra Factory ; Jaanisoo, Jaan ; Kaljusmaa, Riina ; Kelomees, Raivo ; Mäetamm, Marko ; Mälk, Kadri ; Laurits, Peeter Maria ; Linnap, Peeter ; Ladva, Tarmo ; Ojaver, Jüri ; Ojaver, Terje ; Rebane, Tiiu ; Rajangu, Raul ; Ruber, Piia ; Rodgers, Paul ; Paldrok, Al ; Sameli, Margus ; Starkopf, Hannes ; Senka, Sven ; Studio 22 ; Viljus, Mart ; 21E67
Engels & Ests & Russisch
Self-Portrait, Institute for Contemporary Arts, Moscow, 1995
boek